Application of curcumine and its derivatives in the treatment of cardiovascular diseases: a review. Issue 1 (1st January 2021) - Stamenkovska, Mimoza; Hadzi-Petrushev, Nikola; Nikodinovski, Aleksandar; Gagov, Hristo; Atanasova-Panchevska, Natalija; Mitrokhin, Vadim; Kamkin, Andre; Mladenov, Mitko
ABSTRACT: Cardiovascular diseases are the leading cause of death in the world and scientists pay a lot of attention to identify and reveal the mechanisms of their occurrence. Recently, the attention of scientists is focused increasingly on plant derivatives, such as flavonoids and polyphenols, due to their specific biological effects. One of these compounds is curcumin, which has many biological properties. Numerous studies have been performed to understand the molecular basis of the therapeutic properties of curcumin. As a result of these studies, there is considerable evidence to suggest that curcumin may affect signaling pathways associated with the cell growth, proliferation, survival, inflammation, and gene transcription. Antioxidant and anti-inflammatory mechanisms are the two basic mechanisms to which many of the effects of curcumin in various conditions are attributed. Many factors influence the development of heart disease, but one of the main culprits in their occurrence is the inflammatory process. According to recent research, curcumin is an ingredient that could be used in the prevention or treatment of cardiovascular disease. Also, some studies have shown that it has beneficial effects in preventing vascular damage and ischemia. Despite its beneficial and biological properties, it has been proven that curcumin has relatively low bioavailability and low stability in the human body, which limits its therapeutic application. In this regard, several attempts have been made to synthesize curcumin derivatives with improved bioavailability. In this paper, we review the potential and possibilities of using curcumin and its derivatives in the treatment of cardiovascular disease, which would significantly reduce the mortality rate in the population. Based on all of the above, it can be concluded that further studies of animal models and humans are needed to verify current knowledge about the application of curcumin and its derivatives in the treatment of cardiovascular diseases. In this way through these studies more reliable data will be generated concerning the effects of curcumin and its analogs on cellular and subcellular/molecular levels. Prospectively, we believe that this will ground the basis for further improved synthesis of curcumin-analogs, appropriate for the treatment of cardiovascular diseases.